(untitled) (Archive of Conferences, 2021)
The article theoretically examines the impact of cotton particles with conusimone columns to remove large contaminants, based on the results of the analysis of the connection graphs of the parameters. The formula for determining the pulse of impact of a piece of cotton on the surface of a conical column is recommended